Pistot materiaaliseen sensitiivisyyteen:Perinteisestä aktivistiseen kirjontaan - Hernandez Cervantes, Fabiola; Huhmarniemi, Maria (2023)
Cochineal is an insect that has been used for textile dyeing since pre-Hispanic cultures in Mexico. This exposition discusses the use of the cochineal insect as a natural dye for wool and the bridge between ancient indigenous knowledge and contemporary artistic research. A transatlantic connection is created between the Mexican plateau and the Arctic region, merging traditional knowledge, contemporary art, crafting and conceptualisation through an artistic embroidery initiative involving researchers, craft artists and human rights activists living in the province of Lapland in Finland. Documentary photos of artistic practice and research diaries enhance discussion on sustainability, tradition, craftivism, decolonisation and indigenous knowledge. This exposition embraces collaborative craftivism through a group initiative called Embroidered Stances, discussions about material interconnectedness in a web-of-life conceptual structure that includes sheep wool, cactus, cochineal and ancestral knowledge. The endorsement of material sensitivity is narrated into embroideries by the first author Cervantes and discussed, acknowledging complexities within issues of cultural and ecological sustainability.